Relationship between levels of androgen hormones, hirsutism and acne with depression and anxiety in women with polycystic ovary syndrome - Saeideh Mehrabadi; Shahideh Jahanian Sadatmahalleh; Anoshirvan Kazemnejad (Mashhad University of Medical Sciences, 2019)
Introduction: The quality of life in patients with polycystic ovary syndrome is affected by wide variables. Various studies have shown that these patients are at high risk of depression and anxiety. The most important symptoms of polycystic ovary syndrome include hirsutism, acne, and increased androgen hormones. This study was performed with aim to evaluate the relationship between levels of androgen hormones, hirsutism, and acne with depression and anxiety in women with polycystic ovary syndrome. Methods: This case-control study was performed on 53 patients with polycystic ovary syndrome selected by Rotterdam criteria, and 50 healthy women as control group in Tehran Arash Hospital in 2015-2016. The tools of data collection were questionnaire of demographic information, Beck Depression and Anxiety questionnaire, Ferriman - Gallwey Score to assess the degree of hirsutism, Global Acne Grading System, clinical features of hyperandrogenism and laboratory tests' results (Total testosterone, free testosterone, sex hormone binding globulin). Data were analyzed by SPSS software (version 21) and T-test, Chi-square, and Pearson Correlation Coefficient. P<0.05 was considered statistically significant. Results:Mean scores of acne (p=0.02), hirsutism (p<0.001), total testosterone (p=0.008), and free testosterone (p=0.01) were meaningfully higher in patient group than control group. Mean Sex Hormone Binding Globulin level was not significant different in case and control groups (p=0.3). Mean scores of depression (p=0.001) and anxiety (p=0.01) in patient group (20.35±9.82 and 17.35±10.44) were significantly higher than control group (14.46±8.40 and 12.40±9.65). No significant relationship was found between total scores of acne, hirsutism, total testosterone, free testosterone and sex hormone binding globulin with depression and anxiety (p>0.05). Conclusion: Significant increase in the scores of anxiety and depression in patient group compared to control group can be indicative of depressed and anxious mood in patients with polycystic ovary syndrome.